Modelo de Ecosaneamiento para Sostenibilidad y Resiliencia Sociambiental de la Facultad CAREN: caso de desviación de Orina - Naranjo Tapia, Nelson Geovanny (2017)
The research is based on the need to have an eco-sanitation model for sustainability and socio-environmental resilience in the CAREN Faculty, where actions that reduce the high socio-environmental impact caused by inadequate management of organic nitrogenous effluents (urine) were proposed. The problem occurs because no real environmental awareness has been generated in the population. Activities that produce huge disasters which pollute the environment in a specific way in the CAREN Faculty continue to be developed. The aim of this research is to reduce the socio-environmental impact of urine disposal in the CAREN Faculty through an eco sanation model. It establishes the sanitary risk determines the release of wastewater. A model of management of urine release to the environment was identified, identification of uses in productive sustainability, and the design of a prototype of the urine separator system was operationalized. The methodology was based on fieldwork, through the application of a survey which shows the students' approval about the implementation of an eco sanation model that identifies elements that pollute the environment. It has been possible to establish the existence of a sanitary risk that can be mitigated with the proposed management model. The current production of urine is 1 m3 per day, which is diverted to a collection tank. The final disposal of the urine is for agricultural purposes to take advantage of its high content of nitrogen, potassium, calcium, and phosphorus, releasing it in a grass culture with a surface of 1 ha.